Odpowiedzi

2009-11-12T15:21:06+01:00
A) (x + √5)(x - √5) = x^ - √5x + √5x - 5 = x^ - 5
b) (2y - √3)(y+1) = 2y^ + 2y - √3y - √3
c) (a + √2)(a - √3) = a^ - √3a + √2a - √6
d) (2√2 + k)(√2 - k) = 4 + 2√2k + √2k - k^ = 3√2k + 4 - k^
Najlepsza Odpowiedź!
2009-11-12T15:21:46+01:00
Zadanie z mnożenia sum algebraicznych

1.Wykonaj mnożenie, zredukuj wyrazy podobne:
a)(x + √5)(x - √5)=x²-5
b)(2y - √3)(y+1)=2y²+2y-√3y-√3=2y²+(2-√3)y-√3
c)(a + √2)(a - √3)=a²-√3a+√2a-√6=a²+(√2-√3)a-√6
d)(2√2 + k)(√2 - k)=4-2√2k+√2k-k²=4-√2k-k²
2009-11-12T15:28:45+01:00
A) x*x-x*√5+√*x-√5*√5= x²-x√5+x√5-5=x²-5

b)2y*y+2y*1-√3*y-√3*1=2y²+2y-y√3-√3=2y²+(2-√3)y-√3

c)a*a-a√3+√2*a-√2*√6=a²-a√3+a√2-√6=a²-(√3+√2)a-√6

d)2√2*√2-2√2*k+k√2-k*k=2*2-2√2k+√2k-k²=4-√2k-k²